An Update on the Roles of circRNA-ZFR in Human Malignant Tumors - Liu, Lang; Wang, Haicun; Yu, Shaobo; Gao, Xin; Liu, Guanglin; Sun, Dongsheng; Jiang, Xingming (Frontiers in Cell and Developmental Biology, 2022)
CircRNAs (circular RNAs) are single-stranded RNAs that form covalently closed loops and function as important regulatory elements of the genome through multiple mechanisms. Increasing evidence had indicated that circRNAs, which might serve as either oncogenes or tumor suppressors, played vital roles in the pathophysiology of human diseases, especially in tumorigenesis and progression. CircRNA-ZFR (circular RNA zinc finger RNA binding protein) is a circular RNA that had attracted much attention in recent years. It has been found that circRNA-ZFR was abnormally expressed in a variety of malignant tumors, and its dysregulated expression was closely related to tumor stage, cancer metastasis and patients’ prognosis. Recent studies had shown that circRNA-ZFR could regulate the malignant biological behaviors of tumors through various mechanisms; further exploration of circRNA-ZFR expression in tumors and its regulation on malignant biological behaviors such as tumor proliferation, invasion and drug resistance will provide new ideas for clinical tumors diagnosis and treatment.